Ancient Orient and Old Testament - Kitchen, Kenneth A. (1966)
I. Problems and Solutions: 1. AO and ОТ: The Background; 2. Early Hebrew Chronology; 3. Later Hebrew Chronology; 4. Some Historical Problems; 5. Hebrew Contacts with Near Eastern Religions; 6. The Question of Literary Criticism; 7. Principles of Linguistic Study; 8. Further Aspects of Biblical and Oriental Studies. — II. 9. Near Eastern Light on the Biblical Text; 10. Conclusion. Index of Biblical References. Index of Subjects; 185. 6d.